Does the design of a soda tax matter? Evidence from school children in Europe - Selina Gangl (Empirical Economics, 2023)
This paper compares the effects of two different health taxes on soda consumption and the body mass index (BMI) of school children in Europe. Hungary imposed a comprehensive tax on several unhealthy products in 2011. In contrast, France introduced a tax on sodas with sugar or artificial sweeteners, in 2012. To evaluate these taxation designs, I use a flexible semi-parametric difference-in-differences (DID) approach. The results suggest a counter-intuitive increase in soda consumption caused by the tax in Hungary. The effect of the soda tax on soda consumption in France is insignificant. The BMI is not affected by any tax.
Keywords: H20; H30; I12; I18; L66; 330; Soda tax; Consumption; Health; Semi-parametric difference-in-differences; HBSC